Tribological and corrosion behaviors of fluorocarbon coating reinforced with sodium iron titanate platelets and whiskers. Issue 31 (7th January 2020) - Li, Chang; Hu, Yalong; Zhang, Jiazhi; Shen, Liming; Bao, Ningzhong
ABSTRACT: A series of sodium iron titanate (NFTO)–fluorocarbon composite coatings have been prepared with the liquid‐phase blending method. The effects of two types of NFTO, NFTO platelets, and NFTO whiskers, on the tribological and corrosion behaviors of the composite coatings, are systematically studied. The results show that the addition of NFTO can significantly enhance the friction‐reducing and wear resistance performances of the fluorocarbon coating. Under dry sliding, the minimum specific wear rate is 1.67 × 10 −4 mm 3 /Nm for the platelet‐filled composite coatings and 1.15 × 10 −4 mm 3 /Nm for the whisker‐filled composite coatings, respectively, showing a decrease of 83.5 and 88.6% than that of pure coating. Under a simulated seawater environment, the minimum specific wear rate is 5.44 × 10 −5 mm 3 /Nm for the platelet‐filled composite coatings and 0.84 × 10 −5 mm 3 /Nm for the whisker‐filled composite coatings, respectively, showing a decrease of 90.5 and 98.5% than that of pure coating. The morphologies of worn surfaces, wear debris, and transfer films are analyzed, and the corresponding wear resistance mechanisms are discussed. The electrochemical impedance spectroscopy certifies a remarkably improved corrosion resistance of the composite coatings which have been immersed in 3.5 wt % NaCl solution for 30 days. The composite coating reinforced with 7.5 wt % platelets shows the highest resistance of 256.3 × 10 6  Ω·cm 2, approximately two orders of magnitude higher than that of pure coating. © 2020 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48936. Abstract : A series of FEVE composite coatings with significantly enhanced anti‐wear and anti‐corrosion performances are prepared with the addition of sodium iron titanate (NFTO) platelets and whiskers, and the corresponding mechanisms are revealed.